The Effect of Internship Experience and Organizational Involvement on Students’ Work Readiness - Maisya Tusaqdiah; Zaria Tasya; Lingga Aulya Mayori; Puan Indira Rasikha; Ghaniya Yuri Nabila (Penerbit Goodwood, 2026)
Purpose: This research seeks to analyze how internship experience and participation in organizations affect the job preparedness of students at Universitas Maritim Raja Ali Haji. Methodology/Approach: The study employed a quantitative method and was conducted at Universitas Maritim Raja Ali Haji. Data were collected through surveys distributed to 50 active students and analyzed using SPSS software version 22. Results/Findings: The analysis indicates that internship experience has a negative influence, while organizational involvement has a positive relationship with students’ job readiness. However, both variables are statistically insignificant. This is supported by an R² value of 0.073, meaning only 7.3% of the variance in job preparedness is explained by the two factors. Conclusions: Internship experience and organizational involvement do not significantly affect students’ job readiness. This implies that other influential factors exist beyond the scope of this study and should be examined in future research. Limitations: The study is limited by a small sample size, the use of only two independent variables, and reliance solely on questionnaire data. Contribution: The research offers insights for universities and stakeholders in improving higher education policies and internship programs to enhance students’ job preparedness.